2013
DOI: 10.1115/1.4026003
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Inlet Asymmetry on Steam Turbine Exhaust Hood Flows

Abstract: It has been widely recognized for some decades that it is essential to accurately represent the strong coupling between the last stage blades (LSB) and the diffuser inlet, in order to correctly capture the flow through the exhaust hoods of steam turbine low pressure cylinders. This applies to any form of simulation of the flow, i.e., numerical or experimental. The exhaust hood flow structure is highly three-dimensional and appropriate coupling will enable the important influence of this asymmetry to be transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…All have shown that the unsteady flow field can be reproduced with good accuracy with the NLH approach provided sufficient number of harmonics are modeled. The harmonic study carried out in Burton et al [9] has shown the number of harmonics used in the calculations presented in this paper is sufficient.…”
Section: Single Stator Frozenmentioning
confidence: 95%
See 4 more Smart Citations
“…All have shown that the unsteady flow field can be reproduced with good accuracy with the NLH approach provided sufficient number of harmonics are modeled. The harmonic study carried out in Burton et al [9] has shown the number of harmonics used in the calculations presented in this paper is sufficient.…”
Section: Single Stator Frozenmentioning
confidence: 95%
“…A balance must therefore be found between accuracy and computation time. Results from Burton et al [9] showed that three harmonics are sufficient to accurately model the LP exhaust hood interfaces.…”
Section: Substitution Of Eq (3) Into Eq (2) Leads Tomentioning
confidence: 97%
See 3 more Smart Citations